2021
DOI: 10.3390/met11081250
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Microstructure and Performance of B4C Content in B4C/Cu Composite

Abstract: In this paper, boron carbide (B4C) ceramics were added to a copper (Cu) base, to improve the mechanical properties and wear resistance of pure copper. The B4C/Cu composites with different B4C contents, were obtained by mechanical mixing and discharge plasma sintering methods. Scanning electron microscopy (SEM), energy spectrum analysis (EDS), and electron probe microanalysis (EPMA) were used, to observe and analyze the microstructures of the B4C/Cu composites. The influences of the B4C content on the hardness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Since boron carbide ceramic has higher melting point and chemical stability than oxide ceramic, its hardness even outperforms diamond and boron nitride at high temperature, which can improve the high temperature strength of the matrix [16]. Shu et al [17] found that adding 15 wt% of B 4 C to the copper matrix resulted in a hardness of 86 HBW, which is 79.2% higher than that of pure copper, effectively improved the wear resistance of the copper matrix. Bai et al [18] found that when the volume fraction of B 4 C is 40%-70%, composites with relatively low coefficient of thermal expansion in combination with an efficient thermal conductivity will be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Since boron carbide ceramic has higher melting point and chemical stability than oxide ceramic, its hardness even outperforms diamond and boron nitride at high temperature, which can improve the high temperature strength of the matrix [16]. Shu et al [17] found that adding 15 wt% of B 4 C to the copper matrix resulted in a hardness of 86 HBW, which is 79.2% higher than that of pure copper, effectively improved the wear resistance of the copper matrix. Bai et al [18] found that when the volume fraction of B 4 C is 40%-70%, composites with relatively low coefficient of thermal expansion in combination with an efficient thermal conductivity will be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The W(70-90) wt%-Cu alloy has high thermal conductivity and low coefficient of thermal expansion, making it an ideal packaging material for electronic devices. It is, therefore, widely used in integrated circuits and electronic devices [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Bu olumsuzluğun üstesinden gelmek için bakır matrisli kompozit malzemeler önem kazanmaktadır. Shu vd [10]. Cu-B4C kompozitlerini üretip, B4C'nin mikroyapı, sertlik, elektriksel iletkenlik ve aşınma direncine etkisini incelemişlerdir.…”
unclassified